Oxford international primary English student book 2 - Yeomans,Anna; Sarah Snashall (Pakistan: Oxford University Press, 2022)
The Oxford International Primary English Student Book 2 is designed to support young learners in developing their English language skills through engaging and age-appropriate content. It features a mix of stories, illustrations, and interactive activities that promote reading, writing, listening, and speaking. The book emphasizes integrated skills development, ensuring a balanced approach to language learning. It also introduces diverse cultural themes, fostering global awareness among students. Regular assessments are included to monitor progress, and additional resources are provided for teachers to enhance their instructional methods. Overall, this student book serves as an effective tool for cultivating a love for English in primary education.
The Oxford International Primary English Student Book 2 is designed for young learners, providing a comprehensive approach to developing English language skills. The book combines engaging stories, vibrant illustrations, and interactive activities to foster reading, writing, listening, and speaking abilities.
Keywords: Language Skills; Teaching Resources